The damage of unconfined granite edge due to the impact of varying stiffness projectiles - Shah, Qasim Hussain; Hamdani, Adib (Elsevier, 2013)
A rectangular box shaped granite specimen was subjected to varying stiffness projectile impacts on its unconfined edge to investigate the rock damage. Three kinds of projectiles were used, namely chrome steel, copper 102 and pure lead. In comparison to high constraint impact, unconfined edge impact of varying projectile stiffness for brittle targets has not been reported in the literature. Steel, copper and lead projectile impacts revealed that the extent of damage varied depending on the projectile materials. Larger damage on impacted granite’s edge was observed due to copper projectile in comparison to steel and lead projectiles. The experimental results were compared to numerical simulations by using Smooth Particle Hydrodynamics (SPH) available in commercial software LS-DYNA as a finite element tool and they were in good agreement. The SPH model of granite provided good description that double-layer crater was formed as a result of unconfined edge projectile impact which matched the experimental findings well. Threshold value of projectile stiffness was proposed to remain significant factor in damaging unconfined granite’s edge.